The role of family socialization in choosing a marriage partner-Sociogical Analytical Study (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The research presented deals with the phenomenon of marriage, this global phenomenon, which is never without a society, although its manifestations and mechanisms have varied from society to society, and from time to time in society itself. In addition to knowing how the selection process is conducted for marriage and what the family's role is in doing so, by revealing the ways in which family socialization is raised and how it affects the selection process for marriage. The main objective of the research is therefore to highlight the phenomenon as a whole. Therefore, the analytical descriptive approach was used to describe the phenomenon of marriage and analyze its dimensions and factors affecting it